2009
DOI: 10.1590/s1413-86702009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomy, dental caries and periodontal disease in HIV+ patients

Abstract: We studied xerostomy and its correlation with periodontal and dental cavity diseases in HIV patients, through measurement of salivary flow and through variables such as saliva buffer capacity, salivary pH, periodontal index, MDF index, dental carie risk and risk of periodontal disease. One hundred patients were analyzed. They were distributed into two groups: Group I (test) -50 patients evidently HIV + , from whom information was collected and analyzed regarding age, gender, skin color, habits, general and ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 13 publications
5
25
2
6
Order By: Relevance
“…A Tabela 2 apresenta oito estudos referentes à associação entre hipofunção das glândulas salivares/xerostomia e a Terapia Antirretroviral Altamente Ativa (HAART). Três destes encontraram associação entre xerostomia e a referida terapia 1,20,21 ; dois estudaram o uso da terapia que incluía Inibidores de Protease 22,23 , sendo esta associada à xerostomia em um dos trabalhos 22 e, em outro, ao aumento das lesões bucais 23 . Um artigo mostrou associação entre a HAART e o aumento da glândula parótida 2 , sendo que outro estudo observou que a probabilidade de xerostomia era menor em pacientes que faziam uso contínuo da HAART quando comparados aos que faziam uso descontínuo da mesma terapia 24 .…”
Section: Materials E Métodounclassified
See 1 more Smart Citation
“…A Tabela 2 apresenta oito estudos referentes à associação entre hipofunção das glândulas salivares/xerostomia e a Terapia Antirretroviral Altamente Ativa (HAART). Três destes encontraram associação entre xerostomia e a referida terapia 1,20,21 ; dois estudaram o uso da terapia que incluía Inibidores de Protease 22,23 , sendo esta associada à xerostomia em um dos trabalhos 22 e, em outro, ao aumento das lesões bucais 23 . Um artigo mostrou associação entre a HAART e o aumento da glândula parótida 2 , sendo que outro estudo observou que a probabilidade de xerostomia era menor em pacientes que faziam uso contínuo da HAART quando comparados aos que faziam uso descontínuo da mesma terapia 24 .…”
Section: Materials E Métodounclassified
“…A Síndrome da Imunodeficiência Adquirida (AIDS) foi e ainda é uma das patologias de maior interesse para a comunidade científica 1 . A infecção pelo Vírus da Imunodeficiência Humana (HIV) é caracterizada por uma redução gradual e progressiva de linfócitos T CD4+, que, por sua vez, leva a um aumento de infecções oportunistas; estas, invariavelmente, conduzem à morte do paciente 2 .…”
Section: Introductionunclassified
“…According to studies, HIV-positive cases are more susceptible to dental caries when compared to HIV-negative ones (2, 3). The reason may be traced to the increased level of Streptococcus mutans the main pathogen associated with dental caries in HIV-positive cases compared to healthy cases (4).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the buffering capability and pH of saliva decreased significantly in these patients. This may also be considered a factor for the increased number of caries in these patients (2, 7). Today, antiretroviral therapy (ART) is prescribed to treat HIV-positive patients, sometimes for extended periods (8).…”
Section: Introductionmentioning
confidence: 99%
“…Jeganathan et al [15] found that the patient's age and the duration of the HIV infection determine the occurrence of mouth dryness, which in turn is reflected by higher severity of caries and overall deterioration of the quality of life. Chronic inflammation of the salivary glands is observed despite implementation of anti-retroviral therapy, radically inhibiting the secretion of saliva and increasing the dryness of the oral mucosa [17].…”
mentioning
confidence: 99%